Onslaught [large type] : the war with China--the opening battle - Poyer, David (Poyer, David. Tales of the modern Navy., 2018)
"As the U.S. Navy struggles to hold Taiwan, Korea, and Japan against a massive Chinese offensive, USS Savo Island, captained by Dan Lenson, must contend with a fractured crew under attack from an unknown assailant aboard their own ship while facing missile launches from above and below the sea's surface"--